Management in new age: western windows Eastern doors - Sharma, Subhash (New Delhi : New Age International)
Business
Keywords: Management; New Age; Western; windows; Eastern Doors; Reality; Re-construction; Motivation Revisited; Epilogue; HRD; New Age